Artificial Intelligence for the Internet of Everything - Lawless, William; Mittu, Ranjeev; Sofge, Donald; Moskowitz, Ira S; Russell, Stephen, (Information processor) (Academic Press, 2019)
Artificial Intelligence for the Internet of Everything considers the foundations, metrics and applications of IoE systems. It covers whether devices and IoE systems should speak only to each other, to humans or to both. Further, the book explores how IoE systems affect targeted audiences (researchers, machines, robots, users) and society, as well as future ecosystems. It examines the meaning, value and effect that IoT has had and may have on ordinary life, in business, on the battlefield, and with the rise of intelligent and autonomous systems. Based on an artificial intelligence (AI) perspective, this book addresses how IoE affects sensing, perception, cognition and behavior. Each chapter addresses practical, measurement, theoretical and research questions about how these "things" may affect individuals, teams, society or each other. Of particular focus is what may happen when these "things" begin to reason, communicate and act autonomously on their own, whether independently or interdependently with other "things."